Study of residual stresses in Ti-7Al using theory and experiments. (December 2017) - Chatterjee, K.; Ko, J.Y.P.; Weiss, J.T.; Philipp, H.T.; Becker, J.; Purohit, P.; Gruner, S.M.; Beaudoin, A.J.
Highlights: Deformation and resulting residual stresses were studied in a Ti-7Al alloy. Crystal-scale modeling was combined with high energy X-ray diffraction (HEXD). HEXD data was used to initialize the model microstructure and rate sensitivity. Stress values and slip activities are determined at the grain and subgrain level. Prismatic slip was dominant and accurate rate sensitivity was critical to modeling. Graphical abstract: Abstract: Finite element simulations are carried out to follow the evolution of residual stresses in Ti-7Al ( α -hcp) alloy, as developed under an applied stress gradient. A model built upon phenomenological mesoscopic field dislocation mechanics is employed to simulate the deformation behavior. Model predictions are validated with results generated from high energy X-ray diffraction experiments using synchrotron radiation. These experiments provide for important simulation input, viz. grain positions and orientations, and strain rate sensitivities of the prismatic and basal slip systems of Ti-7Al. X-ray diffraction data obtained from individual grains enabled calculation of strain rate sensitivities of the prismatic and basal slip systems and the values are estimated as  ∼ 0.04 and  ∼ 0.02 respectively. Residual stresses at the length scale of individual grains and subgrains are successfully predicted and validated against experimental data. A key achievement of the present work is the measurement and simulation of residual stress gradients within individual grains. Conclusions from this work are that grains deform mainly via prismatic slip, and accurate characterization of rate-sensitivity is needed to model the development of grain-level residual stresses.